(untitled) (Perioperaciina Medicina, 2022)
Background. Currently, one of the most serious complications of acute inflammatory diseases of the abdominal cavity is peritonitis. Objective: to study the development of endothelial dysfunction in experimental peritonitis and compare its correction with a solution of decamethoxine, aminoguadine and L-arginine. Materials and methods of research. The study was conducted on 260 white rats of reproductive age (3 months), animal weight — 180–220 g. Animals were divided into 4 groups. Fecal peritonitis was simulated by introducing a 10 % fecal suspension at a dose of 0.5 ml per 100 g of animal weight to the abdominal cavity of laboratory animals by puncture method. Research results. Pathological increase in vasoconstriction caused by experimental peritonitis was revealed. It was found that the use of solution, consisting of decamethoxine (10 mg/50 ml of solution) and sodium hyaluronate, is an effective method of rehabilitation and the basis for further correction of complications of experimental fecal peritonitis.The use of aminoguadine in combination with the rehabilitation of the abdominal cavity with a solution of decamethoxine had a positive effect on reducing the level of endothelin-1 in the simulated peritonitis. Combination of nitric oxide donor with decamethoxine solution and sodium hyaluronate nitric oxide donor effect on reducing the level of endothelin-1 in the simulated peritonitis. Conclusions: Given the influence of endogenous intoxication on the increase of the marker of vasoconstriction, rehabilitation of the abdominal cavity, the choice of decamethoxine solution (10 mg/50 ml of solution) in the conditions of our study is justified.